Multi-Dimensional Approach to State Regulation of Supply Chain in Innovative Economy - Ildar Ablaev (International Journal of Supply Chain Management, 2018)
Nowadays in the world, one of the main engines of economic development is scientific and technological progress and intellectualization of the main factors of production. The problem is that most post-Soviet states, in particular, Russia need to develop brand new state programs for regulating innovation. Otherwise, the absence of this regulator may lead to an increase in the gap between Russia and developed countries. Thus, the purpose of this article is to define the main directions of the state policy on innovations and focuses on the supply chain economy in Russia. To achieve this goal, some state programs of developed countries, such as the United States of America and European Union (EU) countries, were considered. As a result, the main directions of the state regulation of supply chain in the innovative economy were defined. There are some important aspects were identified, such as boosting innovation activity, improvement of the use of public resources, support of domestic innovative products, increasing the supply chain economys quantity. Because of such economic policy, conditions for the effective functioning of the scientific and technical sphere will be created.Keywords- state regulation, innovation policy, economic development, supply chain, innovative processes.